Learning of teachers - formal and informal learning in TÁMOP projects for development of teacher training programs - Adermann Cserné, Gizella (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In our study we present two consecutive TÁMOP projects aimed to develop teacher training programs and teacher training networks from the aspect of learning processes that took place during these projects – what kind of learning processes has been generated among the implementers and the target group members between 2010 and 2015. We focus on the example of the college of Dunaújváros, also referring to the experience gained in collaboration with the Pannon University, and to the information published through the national meetings of the project. Our study underlines that a wide variety of learning took place in these examples of the projects.